Analysis of interdependence between fiscal and monetary policy in the case of the general budget deficit, Iraq a model - كمال كاظم جواد الشمري; ابتهال احمد عبد عون الشمري (Iraqi Journal for Administrative Sciences, 2024)
The interdependence and coordination between fiscal and monetary policy is necessary to achieve the common goals of both policies of achieving economic stability and achieving acceptable rates of economic growth, but the increase in the budget deficit due to the lack of public revenues or the extraordinary increase in public expenditure (Iraq in recent years), makes the government sometimes resort to reliance on monetary policy and its various tools to finance that deficit. The research dealt with the state of the Iraqi economy as the government used to borrow from the Central Bank or to use the tools of monetary policy, especially the open market in financing the budget deficit and this impacted on foreign reserves with the Central Bank, in this research we conclude that the overlap between the tools of fiscal and monetary policy in Iraq Resulted in an inverse relationship between internal public debt and foreign reserves. One of the main recommendations of the research is the need to coordinate the fiscal and monetary policy in a way that does not limit the efficiency of each of them, as well as the need for the government to diversify sources of non-oil revenues to prevent falling into the problem of dependency global economies.